Regional Investment, Leverage, and Financial Independence in Central Sulawesi - Andi Aidir Arsy; Dewi Salmita; Muhammad Syafaat; Noval; Noor Riefma Hidayah (CV. Sakura Digital Nusantara, 2026)
Purpose - This study examines the association between regional investment, leverage, and regional financial independence within the fiscal decentralization framework. Design/methodology/approach - A quantitative associative approach is employed using pooled panel data from 13 regency and municipal governments in Central Sulawesi Province during 2018–2024. The relationships among variables are analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with WarpPLS. The analysis is grounded in fiscal decentralization theory and agency theory to explain local government financial management behavior. Finding/Results – The results indicate that regional investment and leverage are positively and significantly associated with regional financial independence in the pooled PLS-SEM model. Long-term investment is related to stronger fiscal capacity, while leverage may serve as a supportive financing instrument when managed prudently. Together, both variables explain a moderate proportion of the variation in regional financial independence. Originality/Value - This study contributes empirical evidence on how regional investment and leverage are linked to local fiscal autonomy in Central Sulawesi, an underrepresented provincial context in Indonesian local government finance studies. The findings provide practical insights for local governments to improve productive long-term investment and maintain prudent liability management. This study is limited to one province and two explanatory variables; therefore, future research may expand regional coverage and include governance quality, revenue effectiveness, transfer dependence, and expenditure efficiency.